Health on equal terms? - Västra Götaland, 2005 - Health on equal terms, Västra Götaland - 2005 - Public Health Agency of Sweden; Public Health Agency of Sweden (Region Västra Götaland, 2015)
The survey “Health on equal terms?” is a national survey, conducted every year since 2004.
The Public Health Agency is responsible for the survey and Statistics Sweden (SCB) is responsible for the distribution, collection and registration. During the data collection in 2005, Region Västra Götaland ordered an additional sample for Västra Götaland County.

The additional sample in 2005 included all individuals aged 16-84 years living in Västra Götaland County. A total of 16,281 individuals answered the questionnaire, representing a response rate of 62,4 percent.

The questionnaire consisted a total of 131 questions, covering e.g. issues of health, lifestyle, economic conditions, work and employment, and security and social relations. In addition to data collected through the questionnaire, registry data were also included.

Purpose:

The aim of the national survey was to investigate the health in the population and to show changes in the population's health over time as a follow up of the national health politics. The aim of the additional sample in Västra Götaland County was to investigate the health in the population in Västra Götaland County.

Undersökningen ”Hälsa på lika villkor?” är en stor nationell undersökning som genomförts varje år sedan 2004. Folkhälsomyndigheten ansvarar för undersökningen medan Statistiska centralbyrån (SCB) ansvarar för utskick, insamling och registrering av svar. I samband med undersökningen 2005 beställde Västra Götalandsregionen ett tilläggsurval för Västra Götalands län.

Tilläggsurvalet för 2005 års undersökning inkluderade samtliga invånare 16-84 år i Västra Götalands län. Frågeformuläret besvarades av totalt 16 281 individer inom Västra Götalands län, vilket motsvarade en svarsfrekvens på 62,4 procent.

Blanketten bestod av 75 numrerade frågor, flera av dem hade delfrågor vilket genererade totalt 131 frågor. Frågorna handlade bl.a. om hälsa, levnadsvanor, ekonomiska förhållanden, arbete och sysselsättning samt trygghet och sociala relationer. Förutom variabler som samlats in via frågeblanketten har ett antal registervariabler hämtats från SCB:s register över totalbefolkningen (RTB), utbildningsregistret och inkomst- och taxeringsregistret.

Syfte:

Syftet med den nationella undersökningen var att ta reda på hur Sveriges befolkning mår och lever och även att följa upp den nya folkhälsopolitiken. Syftet med urvalet för Västra Götalands län var att ta reda på hur befolkningen i Västra Götalands län mår och lever.
Hälsa på lika villkor? - Västra Götaland, 2005 - Hälsa på lika villkor, Västra Götaland - 2005
Keywords: Health Services; Hälso- och sjukvård; Physical Examination; Hälsokontroll; Dental Care; Tandvård; Hearing; Hörsel; Life Style; Livsstil; Medicine; Medicin; Exercise; Träning; Population Surveillance; Populationsövervakning; Hearing Loss; Hörselnedsättning; Socioeconomic Factors; Socioekonomiska faktorer; Tinnitus; Öronsusning; Urinary Incontinence; Urininkontinens; Anxiety; Ångest; Overweight; Övervikt; Diet; Kost; Alcohol Drinking; Alkoholkonsumtion; Occupational Health; Arbetshälsa; Work; Arbete; Job Satisfaction; Arbetstillfredsställelse; Asthma; Astma; Diabetes Mellitus; Diabetes; Eczema; Eksem; Public Health; Folkhälsa; Leisure Activities; Fritidsaktiviteter; Cardiovascular Diseases; Kardiovaskulära sjukdomar; Headache; Huvudvärk; Health; Hälsa; Health Status; Hälsotillstånd; Hypertension; Högt blodtryck; Body Weight; Kroppsvikt; Drug Utilization; Läkemedelsförsörjning; Gastrointestinal Diseases; Mag-tarmsjukdomar; Migraine Disorders; Migränsjukdomar; Oral Health; Munhälsa; Depression; Depression; Interpersonal Relations; Mellanmänskliga relationer; Mental Health; Psykisk hälsa; Registries; Register; Smoking; Rökning; Disease; Sjukdom; Pain; Smärta; Tobacco, Smokeless; Rökfri tobak; Social Support; Socialt stöd; Stress, Psychological; Psykologisk stress; Vision, Ocular; Syn; Sleep; Sömn; Sleep Wake Disorders; Sömn- och vakenhetsstörningar; Fatigue; Trötthet; Occupations; Yrken; Occupational Exposure; Yrkesmässig exponering